Gestão de Unidades de Conservação: um estudo de caso do Parque Estadual de Vila Velha - Waltrick, Maria Salete (2001)
Looking for solutions for the preservation of the biological wealth, important for the man's life on earth, the units of conservation were created and they have as objectives the conservation, the accomplishment of scientific researches, the environmental education and the leisure. So that their objectives are reached, their use and administration should be drifted so that their perpetual preservation is guaranteed. it is essential the presence of a determined administration in looking for improvement alternatives, support of the society and important financial resources for their maintenance. The objective of this work is of analyzing, through the case study, the problems faced in the administration of the units of conservation, what take to a deficient administration of the protected areas committing their preservation. Using concepts and beginnings of general domain and bibliographical citations, themes are discussed such as planning, paper of the handling plan, human training, administration responsibility in the units of conservation and the tourism in the units of conservation. After the study of the bibliographical referencial an accompaniment of the problems as was as accomplished faced by the state park of Vila Velha and in the way as it has been administered, well with a relationship among the principal problems faced by the park and for the other units of conservation in the administration of the patrimony of the biodiversity.